Synthesis of Symmetrical and Asymmetrical Azines Encompassing Naphtho[2,1-b]furan by a Novel Approach - K. Veena; M. Ramaiah; G. K. Vanita; T. S. Avinash; V. P. Vaidya (E-Journal of Chemistry)
The starting material 3-nitro-2-acetylnaphtho[2,1-b]furan (2) was obtained by nitration of 2-acetylnaphtho[2,1-b] furan (1), under mild condition. The compound 1 was synthesized by the reaction of 2-hydroxy-1-naphthaldehyde with chloroacetone, where in both condensation and cyclization took place in single step. The reaction of 3-nitro-2-acetylnaphtho[2,1-b]furan (2) with hydrazine hydrate produced corresponding hydrazone (3) in excellent yield, which on treatment with various aromatic aldehydes under different reaction conditions resulted in the formation of symmetrical azines (4a-e) and unsymmetrical azines (5a-e). All the newly synthesized compounds have been characterized by analytical and spectral studies and were screened for antibacterial antibacterial activity against Bacillus subtilus and Alcaligenes fecalies and antifungal activity against Aspergillus nidulans, Aspergillus parasiticus and Aspergillus terrus. The Second Harmonic Generation (SHG) efficiency of some of the synthesized compounds was measured by powder technique using Nd:YAG laser.